Penerapan Model Card Sort untuk Meningkatkan Hasil Belajar Kelas V UPT SDN 18 Mengkendek - Hasnah Hasnah; Ila Israwaty; Andini Andini (STKIP Andi Matappa Pangkep, 2023)
This study aims to determine the improvement of the process and student learning Achievement IPS Payload by applying the card sort learning model. This research approach is a qualitative approach with the type of research is classroom action research. The focus of this research is process focus and results focus. This research was conducted at UPT SD Negeri 18 Mengkendek, Tana Toraja Regency with the research subjects being teachers and fourth grade students of UPT SD Negeri 18 Mengkendek for the academic year 2022/2023, totaling 20 students consisting of 10 male students and 10 female students. This research was conducted in 2 cycles. Each cycle includes the stages of planning, implementation, observation and reflection. From the implementation, data were collected by using observation techniques, learning outcomes tests and documentation. The results of the first cycle of learning indicate that the indicators of success have reached the sufficient category (C) and the second cycle of learning outcomes has reached the good category (B). So it can be concluded that by applying the card sort learning model can improve the process and student learning Achievement IPS Payload in class V UPT SD Negeri 18 Mengkendek Tana Toraja Regency.